2018
DOI: 10.4103/ijccm.ijccm_437_18
|View full text |Cite
|
Sign up to set email alerts
|

Junctional rhythm: A rare sign in leptospirosis

Abstract: Leptospirosis is an important re-emerging infectious disease. Leptospirosis has been estimated to affect tens of millions of humans annually with a case fatality rate ranging from 5% to 25%; however, it is underreported due to the lack of clinical suspicion and barriers to diagnostic capacity. A 33-year-old healthy male presented with a history of fever of 2-day duration. His examination revealed icterus. His workup did not show any significant findings except for a mild transaminitis and a rise in serum creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Which, according to the study of Assimakopoulos SF, et al., is uncommonly seen in patients. In this study, they presented a patient diagnosed with leptospirosis who developed sinus bradyarrhythmia during hospitalization 2,6 . In the study conducted by Mathew et al., encompassing 105 leptospirosis patients, various acute ECG changes were observed.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Which, according to the study of Assimakopoulos SF, et al., is uncommonly seen in patients. In this study, they presented a patient diagnosed with leptospirosis who developed sinus bradyarrhythmia during hospitalization 2,6 . In the study conducted by Mathew et al., encompassing 105 leptospirosis patients, various acute ECG changes were observed.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, they presented a patient diagnosed with leptospirosis who developed sinus bradyarrhythmia during hospitalization. 2,6 In the study conducted by Mathew et al, encompassing 105 leptospirosis patients, various acute ECG changes were observed. These were include sinus tachycardia (34.2%), sinus bradycardia (16.2%), ST-segment elevation (13.2%), atrial fibrillation (AF) (6.31%), ST-segment depression (5.66%), first-degree atrioventricular (A-V) block (4.76%), left bundle branch block (LBBB) (4.76%), incomplete right bundle branch block (RBBB) (4.76%), atrial and ventricular ectopic beats (2.83%), T-wave inversions (2.83%), junctional rhythm (1.90%), low voltage QRS (1.90%), and abnormal QRS-T angle (1.90%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations